Hardness of heart : a contemporary interpretation of the doctrine of sin - Cherbonnier, E. La B. (Edmond La Beaume), 1918-2017. (Garden City, N.Y., Doubleday & Company, Inc., 1955)
This book attempts to correlate the biblical understanding of sin with the facts of modern life. It will argue that the Bible, far from being irrelevant to the twentieth century, is in fact indispensable to it, that the problems of our day raise questions to which only the biblical religion has ever claimed to have an answer. The implication is that the Bible will yield a philosophy of life which can sustain itself on independent grounds. It is often maintained, to the contrary, that many different philosophies appear in the Bible and that to select one of them and label it "biblical" is arbitrary. Actually, however, recent scholarship has disclosed a far greater unity in the Bible than was formerly supposed. The method underlying the present essay has been to ask: What unspoken philosophical assumptions does the Bible make when it is not talking philosophy at all -- that is, about ninety-nine percent of the time? When the answers to this question are correlated, they comprise a remarkably consistent world view, spanning over ten centuries and including scores of writers. It is this over-all unity of philosophical outloook which will be designated herein as "biblical"--Preface
Humanism versus orthodoxy -- Part one : Man, the religious animal. Good and evil : everybody's problem -- Human freedom : to the Greeks, foolishness -- Homo religiosus -- The hallmark of idolatry : a hard heart -- Part two : Partial eclipse of the biblical understanding of sin. Sin misconceived as breaking rules -- Sin misconceived as intrinsic to human nature -- St. Augustine's achievements and mistakes -- Augustine and Pelagius : brothers under the skin -- Part three : Validation of the biblical understanding of sin. Augustine's intentions fulfilled -- Pelagius's intentions fulfilled -- The worship of reason -- Graven images in modern dress -- The hidden gods of cynicism -- Hearts of flesh.
Includes bibliographical footnotes.
Keywords: Sin -- Christianity; Sin